Peran Komunikasi Digital dalam Peningkatan Efisiensi Bisnis - Hadi Sutrisno; Hajarudin Hajarudin (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to analyze the role of digital communication in improving business efficiency by focusing on the use of digital communication tools such as email, chat, and collaboration platforms. The research object consisted of 10 STIE Ganesha students of the employee class who were selected as respondents to provide insight into their experience in using digital communication tools in the context of their work. This research was carried out in May 2024 using a qualitative approach, where data was collected through in-depth interviews and thematic analysis to identify key patterns and themes related to the effectiveness of digital communication compared to traditional communication methods. The results showed that digital communication tools significantly improved operational efficiency for working students, allowing them to complete tasks more quickly and organized. However, the findings also reveal significant challenges, such as information overload and notification distractions, which can reduce productivity and focus. Therefore, while digital communication offers many advantages, it is important for individuals to develop effective management strategies to address these negative potentials, such as notification management and wise time allocation. The implications of this study underscore the importance of a deep understanding of digital communication tools and their effective application to maximize productivity in the modern business environment.